2014
DOI: 10.4103/2277-9175.125751
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between workplace and occupational burnout syndrome in nurses

Abstract: Background:This study was conducted to determine the effect of nurses’ workplace on burnout syndrome among nurses working in Isfahan's Alzahra Hospital as a reference and typical university affiliated hospital, in 2010.Materials and Methods:In this cross-sectional study, 100 nurses were randomly selected among those working in emergency, orthopedic, dialysis wards and intensive care unit (ICU). Required data on determination of occupational burnout rate among the nurses of these wards were collected using Masl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 9 publications
1
16
0
3
Order By: Relevance
“…In addition, researches in Portugal indicate that work overload is one of the predisposing factors of burnout (Queiros et al, 2013). Finally, research conducted in Iran has shown that nurses from departments more exposed to workloads, such as emergency services, are more likely to become victims of occupational burnout (Ahmadi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researches in Portugal indicate that work overload is one of the predisposing factors of burnout (Queiros et al, 2013). Finally, research conducted in Iran has shown that nurses from departments more exposed to workloads, such as emergency services, are more likely to become victims of occupational burnout (Ahmadi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They reported the job stress less than the average level. 18 Probably, because the task of faculty members is to promote knowledge and research in the community and it was relevant to their expertise and interest led to them feel less stress.…”
Section: Discussionmentioning
confidence: 99%
“…They showed the different amount of job stress in various colleges; on the other hand, showing more frequency of mental pressure in the colleges that the faculty members were highly involving with students. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Em um trabalho de revisão da literatura, foram identifi cados onze estudos que fi zeram o levantamento dos fatores sociodemográfi cos e ocupacionais relacionados à síndrome de Burnout nos trabalhadores de enfermagem que atuam em hospitais, sendo seis internacionais (Ahmadi, Azizkhani, & Basravi, 2014;Higashiguchi et al, 1999;Ilhan, Durukan, Taner, Maral, & Bumin, 2008;Lin, St John, & McVeigh, 2009;Linde, Martínez, & Cervantes, 2005;Wang, Liu, & Wang, 2013) e cinco nacionais (Meneghini, Paz, & Lautert, 2011;Moreira, Magnago, Sakae, & Magajewski, 2009;Rissardo & Gasparino, 2013;Silva & Carlotto, 2008;Tavares, Souza, Silva, & Kestenberg, 2014). Apenas um estudo foi realizado com profi ssionais de Unidades Básicas de Saúde (UBSs) (Holmes, Alves, Holmes,Viana, & Santos, 2014).…”
unclassified
“…Duas pesquisas mostraram que os trabalhadores que atuavam nos setores de internação apresentaram maiores pontuações em despersonalização (Higashiguchi et al, 1999;Linde et al, 2005). Quatro estudos divergiram desse resultado, pois os profi ssionais com maiores chances de serem acometidos pela síndrome trabalhavam em setores como o Centro de Terapia Intensiva (CTI), Pronto-atendimento e Centro Cirúrgico (Ahmadi et al, 2014;Ilhan et al, 2008;Lin et al, 2009;Tavares et al, 2014). Quanto à carga horária de trabalho, uma pesquisa relatou que quanto maior era o tempo de trabalho, maior era o risco de ocorrência da síndrome (Ilhan et al, 2008).…”
unclassified